Detection and characterization of cucumber mosaic virus infecting ginger (Zingiber officinale Rosc.) and turmeric (Curcuma longa L.) in Peninsular Malaysia - Muhammad, Buhari; Vadamalai, Ganesan; Lau, Wei Hong; Kong, Lih Ling (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Ginger (Zingiber officinale Rosc.) is native to Asia but is now cultivated worldwide. It is of culinary and medicinal importance and it is among the most valued and widely cultivated spice crops worldwide. Turmeric (Curcuma longa L.) originated in India, and now cultivated throughout the tropical Asia and in other subtropical and tropical parts of the world. It is used mostly as spice and dye. Cucumber mosaic virus (CMV), a type species of the genus Cucumovirus, has the widest host range of all the known plant viruses, infecting more than 1000 plant species and have been reported lead to 100% crop loss. This study was therefore conceived to investigate CMV infection in ginger and turmeric in Malaysia. Samples of ginger and turmeric plants showing virus-like infection symptoms were collected from selected farms in the States of Perak and Selangor, Malaysia. Total nucleic acid was extracted using CTAB buffer. Reverse-transcription polymerase chain reaction (RT-PCR) using CMV specific primers, was carried out to detect the virus. The amplified PCR products were then cloned and sequenced. Phylogenetic analysis was carried out using MEGA 7.0 and trees were generated using neighbour-joining method. Sequence analysis showed that the CMV isolates of Malaysia were closely related to those of China (banana) and Thailand (cucumber) with 95% to 96% sequence similarity respectively. The sequence analysis placed the Malaysian CMV isolates into Subgroup IB, hence affirming the presence of the Subgroup IB as the Asian strain. This study revealed the presence of CMV in ginger and turmeric in Peninsular Malaysia thereby widening the host range of CMV to Zingiberaceae family.